Assessment of knowledge and attitudes regarding pneumonia disease among patients at AL-Suwaira General Hospital in AL-Suwaira City - Fatima Samir Abdel.Razaq; Mayada Obaid; Nagham Mohammed (Microbes and Infectious Diseases)
Background: Pneumonia is an inflammatory condition that affects the lung and mainly affects the microscopic air sacs known as alveoli. They usually occur as a result of infections caused by viruses or bacteria, and to a lesser extent other microbes, some medications, and other medical conditions such as autoimmune diseases. Bacterial causes of pneumonia the most common bacterial causes of community-acquired pneumonia include Streptococcus pneumoniae. Pneumonia can be caused by many different types of microorganisms, including: Viruses (most common) Bacteria or germs. The severity of pneumonia can range from mild to very severe and life-threatening. It is more dangerous for infants and young children, people older than 65, and people with health problems or a weak immune system. Methods: A cross-sectional study of 100 a random sample of residents was conducted in this study. During February to March 2024. Knowledge and attitudes were assessed by using typical self-administered questionnaire. Descriptive analyses were used to express the results. Results: A total of 100 participants responded to the questionnaire, Overall, participants demonstrated good knowledge and positive attitudes towards Pneumonia. In this study, the demographic characteristics of the study participants indicate a predominance of younger individuals, with the majority aged less than 29 years. Middle-aged individuals (23–40 years) constitute a smaller proportion, while those aged 41–50 years and over 50 years are relatively fewer. There is a slightly higher representation of females compared to males. Conclusion: Participants exhibit diverse educational backgrounds, ranging from no formal education to bachelor's degrees, with the majority holding bachelor's degrees.